STRATEGI ADAPTASI EKONOMI MASYARAKAT DALAM MENGHADAPI FLUKTUASI HARGA KELAPA SAWIT ( STUDI KASUS PADA MASYARAKAT NAGARI BUNUIK, KEC. KINALI, KAB PASAMAN BARAT) - Lisa Monica; Sandra Dewi (CV. Adiba Aisha Amira, 2025)
This research aims to determine and describe the economic adaptation strategies used by the Nagari Bunuik Community in facing fluctuations in palm oil prices. The informants in this research were 20 people from the community who own oil palm land and are Muslim. The type of research used is qualitative, namely research where the data is in the form of words (not numbers) originating from interviews, report notes, documents and so on. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results of this research show that there are several strategies implemented by the farming community in dealing with fluctuations in palm oil prices. The active strategies implemented by the community are selling goods online, being a carpenter, opening a small business (UMKM), doing odd jobs (home craftsmen), agricultural laborers, working as organ employees. And passive strategies such as using the house yard as a place to grow crops, using the house yard to raise livestock and fish, and taking debt from cooperatives to meet basic needs. There are several obstacles faced by the Nagari Bunuik Community in implementing the strategy, namely limited capital and unequal competition.